Agricultural Change in India: Emerging Scenarios - Singh, Ravi S.; Tripathi, Parmanand (National Geographical Journal of India, 2022)
The situation of Indian agriculture has undergone considerable changes since 1990s due to economic reforms introduced in 1991 and the consequent economic liberalisation. After the implementation of micro economic framework, public and private sectors have shown interest in direct investment in rural areas to take advantage of changes in rural enterprises, liberal trade and market policy, etc. Desirable changes in farm technology and new economic policy have contributed to the rise in agriculture productions. Many scholars have tried to study the impact of economic liberalisation on Indian economy and quite a few of them have specifically studied the impacts on Indian agriculture. The present attempt is to critically review them. Our analysis reveals that after the initiation of the economic reforms, rural economy has got gradually integrated and has witnessed changes in the nature practiced agriculture, especially during last two and half decades.